ENDOCRINE AND IMMUNOLOGICAL ALTERATIONS IN SEVERE TRAUMA: CONTEMPORARY BIOMARKERS, PROGNOSTIC FACTORS, AND CLINICAL IMPLICATIONS - Radović, Filip; Ćurčić, Mihajlo; Rudić, Marija; Drakul, Ana; Radanović, Dražen; Misić Mandić, Vanja; Giljača, Sonja; Slijepčević, Nikola (HEALTH CARE, 2026)
Severe trauma triggers a complex and dynamic response of the organism that includes simultaneous endocrine, immunological and metabolic alterations with a direct impact on the clinical course and treatment outcome. Hypothalamic-Pituitary-Adrenal (HPA) axis activation, changes in the secretion of catecholamine, disorders of the thyroid function and imbalance of the inflammatory response are key components of the systemic response to traumatic stress. The aim of this review article was to systematize endocrine and immunological biomarkers that have prognostic relevance in patients with severe trauma based on contemporary literature, as well as to review their clinical implications in intensive care medicine. Relevant papers published in the period 2014 to 2025 were reviewed in order to analyze changes in cortisol and catecholamine concentrations, Critical Illness-related Corticosteroid Insufficiency (CIRCI) Syndrome, Non-Thyroid Illness Syndrome (NTIS), as well as inflammatory biomarkers such as Interleukin-6 and C-reactive protein. Special attention was paid to their role in predicting mortality, development of multiple organ dysfunction, respiratory deterioration and septic complications. Available data indicate that early disorders of endocrine axes, especially abnormal patterns of cortisol and thyroid reactions have a significant prognostic values, while inflammatory and transcriptomic biomarkers allow more precise risk stratification in the early stages of critical disease. The integration of endocrine, immunological and metabolic biomarkers with clinical parameters and demographic characteristics of patients is the basis of a modern, personalized approach in the treatment of severe trauma. Further research should be directed towards standardization of diagnostic criteria, optimal sampling time and evaluation of therapeutic interventions, with the aim of improving outcomes and reducing mortality in critically ill patients.
Keywords: trauma, endocrine biomarkers, immunological biomarkers, prognosis, critical condition